Identifikasi Dan Inventarisasi Jenis Tanaman Umbi-Umbian Yang Berpotensi Sebagai Sumber Karbohidrat Alternatif Di Kabupaten Serdang Bedagai - Sihol Marito Sibuea; Emmy Harso Kardhinata; Syafruddin Ilyas (Jurnal Agroekoteknologi, 2014)
Dependence on rice as a food source can be reduced by diversification by utilizing tuberous cropsas a potential alternative source of carbohydrates. In Indonesia there are several types of tuberouscrops that have not been consumed as an alternative carbohydrate source. The objective of thisresearch is to obtain an overview of tuberous plants diversity, distribution and cultivationtechniques as an alternative sourceof carbohydrate. This research was conducted at the SerdangBedagai Regency from July to August 2013. The data was collected through survey methodat 3 (three) districts with 3 (three) villages for each. Sampling was done based on judgmentalsampling and accidental sampling. The research found some tuberous crops such as Dioscoreaalata., Dioscorea esculenta.,Colocasia esculenta, Xantosoma sagittifolium, Canna edulis,Maranta arundinacea, Amorphophallus campanulatus, Some crops grow on orchard and some ofthem have been cultivated intensively by farmers.Keyword : identification, inventory, tuberous crops